1993
DOI: 10.1111/j.1365-2826.1993.tb00358.x
|View full text |Cite
|
Sign up to set email alerts
|

The Maintenance of Normal Parturition in the Rat Requires Neurohypophysial Oxytocin

Abstract: The neuropeptide oxytocin has long been known as a potent contractor of the uterus. However, it has remained difficult to attribute a definite role for neurohypophysial oxytocin in either the initiation or continuation of labour. Most recently, Lefebvre and colleagues have suggested that oxytocin produced in the uterus, rather than in the hypothalamus, may be more important in parturition since at term the uterus of the rat contains 70-fold more mRNA for oxytocin than the hypothalamus, and this disappears at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“…Pulsatile i.v. injection of oxytocin (OXT 1 mU (2 ng; 2 pmoles) every 10 min) after a single injection of morphine after the birth of pup 2 fully restored the progress of normal parturition; continuous infusion (not shown) of the same total dose of oxytocin was ineffective (data from Luckman et al 1993, Antonijevic et al 1995a. The prolonged inhibitory action of the oxytocin antagonist clearly indicates an important role for oxytocin in promoting parturition.…”
Section: Progress Of Deliverymentioning
confidence: 99%
See 3 more Smart Citations
“…Pulsatile i.v. injection of oxytocin (OXT 1 mU (2 ng; 2 pmoles) every 10 min) after a single injection of morphine after the birth of pup 2 fully restored the progress of normal parturition; continuous infusion (not shown) of the same total dose of oxytocin was ineffective (data from Luckman et al 1993, Antonijevic et al 1995a. The prolonged inhibitory action of the oxytocin antagonist clearly indicates an important role for oxytocin in promoting parturition.…”
Section: Progress Of Deliverymentioning
confidence: 99%
“…The pulsatile secretion derives from the synchronised intense bursting activity of oxytocin neurones in the hypothalamus in the rat and rabbit (Summerlee 1981, O'Byrne et al 1986, activity similar to that in the rat during reflex milk ejection in response to suckling. The increased electrical activity is accompanied by induction in these neurones of the immediate-early gene c-fos, an indicator of trans-synaptic activation of the neurones, and consequent prominent expression of the protein product Fos in the nuclei of oxytocin cells (Luckman et al 1993). Furthermore, expression of the oxytocin gene in supraoptic neurones is stimulated at parturition (Douglas et al 1998), while it is controversial whether expression is increased in pregnancy (Horwitz et al 1994, Douglas et al 1998.…”
Section: Parturition In the Ratmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulsatile neurohypophysial oxytocin release is required for the maintenance of normal parturition (Luckman et al 1993), and inhibition of oxytocin release by antagonists has been shown to prolong the expulsive phase in rats (Antonijevic et al 1995) and guinea pigs (Schellenberg 1995). In the pig, prolonged parturition is associated with low basal and peak levels of oxytocin during the expulsive phase (Castren et al 1993).…”
Section: Introductionmentioning
confidence: 99%